The Relationship Between Smoking Status And Diabetic Foot Severity - Surya, Nadhea Debrinita; Jonny Setiawan; Rensa (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Diabetes mellitus is a chronic metabolic disease which happens to be the 7th leading cause of death worldwide. In Indonesia, 6.9% of population aged Â³ 15 years old suffers from this disease. Diabetic foot is one of the complication of diabetes mellitus which has high mortality and morbidity level. Smoking is an addictive behavior that is really common in Indonesia. Components inside a cigarette, such as nicotine, can contribute in determining the prognosis of diabetic foot through various mechanism. This study aims to investigate the association between smoking status and the severity degree of diabetic foot. This study is an observational analytic study using a cross-sectional approach. Data collection was conducted on January 2019 until July 2019 in RSUK Pesanggrahan and Atma Jaya Hospital Jakarta. The research data was obtained through interviews with diabetic foot patients and medical record reading. Data was analyzed using the chi-square method. There were 40 patients eligible to be the subject of this study. The smoker status with the most distribution was moderate smoker (27.5%) and severity degree of diabetic foot with most distribution was Wagner 3 (25%). Bivariate analysis showed that there was a significant association between smoking status and severity degree of diabetic foot (p < 0.001). In conclusion, there is a significant association between smoking status and the severity degree of diabetic foot. Therefore, education regarding the importance of smoking cessation to diabetic foot patients should be done in order to improve the prognosis of diabetic foot patients.